Treatment Effect of Ergocalciferol on Bone Metabolism Indexes and Parathyroid Hormone in Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2018)
Introduction. Vitamin D deficiency is a common problem in end-stage renal disease patients under hemodialysis. Both active and nutritional vitamin D supplementation have been recommended for its treatment. In this study we aimed to evaluate the effects of treatment with ergocalciferol on bone metabolism indexes in hemodialysis patients. Materials and Methods. In a randomized controlled trial, 40 hemodialysis patients were randomly allocated to the intervention (n = 20) and placebo (n = 20) groups. During the study, 4 patients in the placebo and 1 in the intervention group were excluded. Patients received calcitriol, 0.25 mg/d, with ergocalciferol, 50 000 IU, or placebo weekly for 3 months. Serum levels of 25-hydroxyvitamin D, calcium, parathyroid hormone, and alkaline phosphatase were measured before and after treatment. Results. 25-hydroxyvitamin D levels were significantly improved in the intervention group (12.00 ± 4.90 ng/mL versus 29.89 ± 9.48 ng/mL, P < .001), but the placebo group had no improvement (14.23 ± 7.62 ng/mL versus 13.87 ± 8.04 ng/mL, P > .05). There was no significant changes in serum calcium, parathyroid hormone, or alkaline phosphatase levels in each group. Eight patients (42.1%) in the intervention compared to zero cases in the placebo group had normal 25-hydroxyvitamin D levels after treatment (P = .004). No cases of hypercalcemia were seen in the studied patients. Conclusions. Treatment with ergocalciferol could significantly improve vitamin D deficiency with no significant effects of serum calcium or parathyroid hormone levels.